Adaptive Effects of Seeing Green Environment on Psychophysiological Parameters When Walking or Running - Briki, Walid; Majed, Lina (Frontiers in Psychology, 2019)
Several studies have investigated the influence of perceiving colors on affective outcomes and/or performance. However, the effects of seeing colors on self-selected behaviors have received little attention from physiologists and psychologists. Therefore, the present study aimed at examining whether exposure to green and red environments could influence affective judgments, perception of effort, heart rate, and gait speeds when walking and running at a self-selected pace. Participants were randomly assigned to one of the three experimental conditions: Green, red, or white (neutral) environment. The experimental task consisted in a 20-minute trial of either walking (Study 1) or running (Study 2) at the most comfortable speed on a treadmill surrounded by three large HD TV screens displaying specific properties of the studied colors. Study 1 revealed that walking in a green environment induced a significant reduction in heart rate values as compared to the red and white conditions although no differences in gait speed were found. This corroborates the calming and relaxing effect of green on the human organism. Study 2 showed that running in a green environment was associated with an increased level of perceived exertion at similar speeds (compared to other color conditions), while exposure to red induced a significant decrease in the level of tension. In both studies, the preferred gait speed was not affected by the colored environment which is discussed in relation to the energy-conservation principle. Furthermore, both studies showed that performing a 20-minute walk or run at preferred pace presented beneficial mood changes. Implications of the effects of self-selected exercise under colored environments on human functioning are addressed in the discussion.